Establishing and maintaining social connectivity: An understanding of the lived experiences of older adults residing in regional and rural communities. (30th April 2015) - Buys, Laurie; Burton, Lorelle; Cuthill, Michael; Hogan, Anthony; Wilson, Bruce; Baker, Douglas
Abstract Objective To better understand how to plan for an ageing demographic that resides in ever‐changing community typologies. Design Semi‐structured in‐depth interviews. Setting Community settings in rural and regional towns in Queensland. Participants Twenty‐two people aged over 65 years living in regional and rural Australia. Interventions Qualitative study of social connectedness. Main outcome measure(s) Thematic qualitative analysis. Results Formal and informal social contact, through family, friends and social groups, was found to be important to the everyday lives of the participants. Conclusions Social connections for older adults are important in maintaining independence and community engagement.